An undifferentiated carcinoma at Klatskin-position with long-term complete remission after chemotherapy - Köhler, Bruno Christian; Goeppert, Benjamin; Waldburger, Nina; Schlamp, Kai; Sauer, Peter; Jäger, Dirk; Weiss, Karl Heinz; Macher-Göppinger, Stephan; Schirmacher, Peter; Springfeld, Christoph (OncoTarget, 2018)
Neoplasms anatomically adjacent to the bile duct usually derive from malignantly transformed cholangiocytes forming cholangiocarcinoma (CCA). CCAs are divided in extrahepatic (eCCA) and intrahepatic (iCCA) tumors. Patients with irresectable CCAs are treated with systemic chemotherapy and have an unfavorable prognosis with a median survival of about one year. Here, we report a case of an undifferentiated carcinoma in Klatskin-position with long-term remission after systemic chemotherapy.